Estimation of Prospects Related to Developing Tourism and Recreational Services in the Krasnoyarsk Territory - ZLOTNIKOV, Maxim Sergyeyevich; TELNYKH, Victoria Valerievna; MUTOVIN, Sergey Illarionovich; DEMCHENKO, Svetlana Kapitonovna; SUSLOVA, Julia Ju. (Journal of Environmental Management and Tourism; Vol 8 No 2 (2017): JEMT Volume VIII Issue 2(18) Spring 2017DO - 10.14505//jemt.v8.2(18).09, 2017)
In spite of the unique character of tourism resources, the development of the tourism and recreational area of the Krasnoyarsk Territory is restrained, however it has lately become imminent. It is obvious that it is necessary to develop and take measures on developing the tourism and recreational area. In this context it is actual to research and reveal opportunities related to developing the tourism and recreational activity of the Krasnoyarsk Territory. The conducted analysis and estimation give an opportunity to develop models related to the development of tourism and recreational activity on the territory of central areas of the Krasnoyarsk Territory.